Effect of organic linkers and graphene loading on ternary metal organic framework composite for asymmetric supercapacitor application - Amir Luqman, Sanusi (2023)
Supercapacitors (SCs) are energy storage devices with high power density (PD), medium energy density (ED), fast recharge capability, and long cycle life. There are fundamentally two types of energy storage mechanisms in supercapacitors which are electrical double- layer capacitors (EDLCs) and pseudocapacitors (PCs). A third type, called battery – supercapacitor hybrid (BSH), combines the EDLC and PC mechanism. The EDLC stores charge by the reverse accumulation of electric charges at an electrode-electrolyte interface and are non-faradaic, whereas the PC stores charge through a faradaic reaction within a few layers of the electrode. Asymmetric supercapacitors (ASCs) are fabricated using one of its electrodes of PC materials and the other one is EDLC material, combining their beneficial effects. This research pursues the synthesis and characterisation of PC material precursors, which are Co(NO3)2·6H2O, Cu(NO3)2, and Ni(NO3)2·6H2O to form a ternary metal-organic framework (MOF) with different organic linkers, which are terephthalic, trimellitic, and pyromellitic acids via hydrothermal method. The MOF was further modified with N-doped graphene (NG) to enhance the capacitive properties of the SC electrode. The materials were characterised by field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, gas adsorption studies, and thermogravimetric analysis (TGA). FESEM- EDX showed the presence of the corresponding metal precursor elements in the frameworks (i.e., cobalt (Co), copper (Cu), and nickel (Ni)). The XRD analysis showed the crystalline structures of the Co/Cu/Ni-MOF samples, except for Co/Cu/Ni-tri. The FTIR results showed the interaction of the functional groups present in the MOF, including O-H, C-H, C=C, Cu-O, Co-O, and Ni-O vibrational bands. According to the Brunauer-Emmett-Teller (BET) analysis, Co/Cu/Ni-tetra possessed a typical type IV curve, displaying a combination of micropores and mesopores in the MOF. The TGA demonstrated the degradation peaks in the MOF samples with the corresponding temperature, and Co/Cu/Ni-tetra experienced four stages of weight loss in the temperature range of 25–900 ℃ with a final residue of 36%. The electrochemical properties of the materials were evaluated using cyclic voltammetry (CV), galvanostatic charge-discharge cycling (CDC), and electrochemical impedance spectroscopy (EIS). The ternary MOF prepared using pyromellitic acid as a linker and modified with 3 wt% NG (Co/Cu/Ni-tetra/NG-3%) demonstrated the best electrochemical performance with a specific capacitance (CS) of 1,136 F g-1 at 1 A g-1 in 6 M KOH electrolyte. The ASCs were fabricated using Co/Cu/Ni-tetra/NG-3% as a positive electrode and activated carbon (AC) as a negative electrode. The Co/Cu/Ni-tetra/NG-3%//AC in 6 M KOH gave a high ED of 30.4 Wh kg-1 at PD 850 W kg-1, whereas in PVP-KOH gel polymer electrolyte, the ASC recorded ED of 21.6 Wh kg-1 at PD of 950 W kg-1. The ASC stability was much better in 6 M KOH with ~80% retention, whereas ~60% retention was recorded in PVP- KOH after 1,000 cycles due to the better electrolyte ion movement in the cell.